Influence of tinting on physiological and keeping quality parameters of tuberose (Polianthus tuberosa) spikes - GUPTA, ARADHIKA; JHANJI, SHALINI (The Indian Journal of Agricultural Sciences, 2021)
Tinting adds not only variation to flower colours but also to economy of farmers. The different food colours are being used for tinting but little is known about their action. So, the present investigation to evaluate the effect of different food colours on physiological and keeping quality parameters of tuberose (Polianthus tuberosa L.) spikes was conducted at Punjab Agricultural University during 2017-18. The tuberose spikes cv. Prajwal were tinted with food dyes, viz. Apple green, Classic blue, Orange red and Rose pink @ 1% alone and supplemented with sucrose (2%) and citric acid (300 ppm) for 1 and 2 hrs. Tinting had no adverse effect on vase life although other quality parameters, viz. change in weight, dye solution uptake, opening of floret, number of florets drop/spike and water uptake were affected. Based on number of floret drop/spike and floret opening, spikes tinted with Apple green and Classic blue dye solution supplemented with sucrose and citric acid had more acceptability than those tinted with Rose pink and Orange red. The better acceptability of Apple green and Classic blue tinted spikes was associated with more membrane stability index, total soluble protein and total soluble sugar content which decreased with senescence (at the end of vase life). Thus, tinting with Apple green and Classic blue for 1 h in supplemented solution can add colour to tuberose spikes without having any adverse effect on its post-harvest attributes.